2022
DOI: 10.3389/fpls.2022.873480
|View full text |Cite
|
Sign up to set email alerts
|

Specific Bacterial Pathogen Phytosensing Is Enabled by a Synthetic Promoter-Transcription Factor System in Potato

Abstract: Phytosensors are genetically engineered plant-based sensors that feature synthetic promoters fused to reporter genes to sense and report the presence of specific biotic and abiotic stressors on plants. However, when induced reporter gene output is below detectable limits, owing to relatively weak promoters, the phytosensor may not function as intended. Here, we show modifications to the system to amplify reporter gene signal by using a synthetic transcription factor gene driven by a plant pathogen-inducible sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 37 publications
(56 reference statements)
0
10
0
Order By: Relevance
“…As high-throughput sequencing continues to advance, it will become easier to elucidate the tissue-specific or cell-specific expression of the TF complex through techniques using single-cell analysis ( Dorrity et al., 2021 ; Marand et al., 2021 ; Zhang et al., 2021 ), allowing the use of TF-modulation of synthetic promoters in plant systems ( Belcher et al., 2020 ). The synthetic neurospora-based ‘Q-system’ has previously been applied to enhance synthetic promoters to tune signal specificity and sensitivity in Arabidopsis and potato ( Persad et al., 2020 ; Persad-Russell et al., 2022 ). Modifying or identifying a similar orthogonal system could help to improve synthetic promoter activity in other species such as poplar.…”
Section: Discussionmentioning
confidence: 99%
“…As high-throughput sequencing continues to advance, it will become easier to elucidate the tissue-specific or cell-specific expression of the TF complex through techniques using single-cell analysis ( Dorrity et al., 2021 ; Marand et al., 2021 ; Zhang et al., 2021 ), allowing the use of TF-modulation of synthetic promoters in plant systems ( Belcher et al., 2020 ). The synthetic neurospora-based ‘Q-system’ has previously been applied to enhance synthetic promoters to tune signal specificity and sensitivity in Arabidopsis and potato ( Persad et al., 2020 ; Persad-Russell et al., 2022 ). Modifying or identifying a similar orthogonal system could help to improve synthetic promoter activity in other species such as poplar.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the majority of the ClNF-Y genes were induced by Fon , and the pathogen-induced expression was highly evident in roots ( Figure 7 C). Among these pathogen-inducible ClNF-Y genes, the ClNF-YA1 , -YB8 , and -YB9 promoters harbor a pathogen-inducible Box S element ( Figure 4 ), which is known to confer a high level of expression of the target genes in response to elicitors, oomycetes, and bacterial pathogens [ 70 , 71 , 72 ]. Functional studies in transgenic Arabidopsis revealed that 6 ClNF-Y genes play a role in disease resistance ( Figure 9 and Figure 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Reads were aligned to the Populus trichocarpa v3.0 genome (https://phytozome-next.jgi.doe.gov/info/Ptrichocarpa_ v3_0), using Bowtie 2 (Langmead and Salzberg, 2012). Aligned reads mapped to genome features were counted using htseq-count function in HTSeq 2.0 (Putri et al, 2022). Differential expression gene (DEG) analysis was performed using DESeq2 (Love et al, 2014).…”
Section: Rna-seq and Data Analysismentioning
confidence: 99%
“…However, in synthetic promoters, the small number of specific CREs without non‐essential elements allows researchers to off‐target binding of transcription factors and focus on valuable responses, leading to more practical applications. In a number of recent studies, synthetic promoters have been applied to effectively manage gene editing, transgenic crop improvement, and orthogonal biosensor construction (Moreno‐Gimenez et al ., 2022; Oliva et al ., 2019; Persad et al ., 2020; Persad‐Russell et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%